PERAN KEJAKSAAN DALAM PENEGAKAN HUKUM TENTANG CYBER CRIME DI CABANG KECAJAKSAAN NEGERI DELI SERDANG DI LABUHAN DELI - Rusydi Irfan (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2026)
This study analyzes the role of the Deli Serdang District Prosecutor’s Office Branch in Labuhan Deli in enforcing the law against cybercrime, particularly illegal access and phishing. It employed an empirical legal method with a qualitative, descriptive-analytical approach. Primary data were obtained through interviews with prosecutors handling cybercrime cases, while secondary data were drawn from relevant legislation and scholarly articles. The findings demonstrate that the Prosecutor’s Office performs a strategic role through case-file examination, issuance of P-19 instructions, declaration of complete case files through P-21, preparation of indictments, evidentiary presentation at trial, and execution of final court judgments. Electronic evidence, including communication records, transaction data, Internet Protocol addresses, digital devices, and digital forensic examination results, constitutes the principal basis for linking offenders to criminal conduct. Law-enforcement effectiveness remains constrained by false identities, Virtual Private Networks, overseas servers, deletion of digital traces, delayed victim reporting, limited technical competence, and inadequate forensic facilities. This study emphasizes that strengthening prosecutorial capacity, standardizing electronic-evidence management, improving interagency coordination, and expanding digital forensic support are essential to enhancing prosecution quality. Its novelty lies in empirically mapping cybercrime pre-prosecution and prosecution processes at the branch level of the Prosecutor’s Office within a specific local institutional context.Keywords: Cybercrime; Digital Forensics; Electronic Evidence; Law Enforcement; Prosecutor’s Office